From the Netherlands to Batavia: The Foundation of Freemasonry in Nusantara During the 18th Century - Faizal Arifin; Endi Aulia Garadian (Tarikhuna: Journal of History and History Education, 2025)
Freemasonry in Nusantara predates its documented expansion in the 20th century, which saw the involvement of Dutch and priyayi (Javanese aristocracy) elites. Its origins can be traced to the mid-18th century, specifically to the establishment of the Groot Loge (Grand Lodge) in the Netherlands in 1756. This research investigates the early dissemination of Freemasonry in Nusantara, marking the foundational phase of the movement. It explores the spread of the movement through member networks and how emerging community associations were later restructured into formal lodges or kring (circles) during the era of the Dutch East India Company (VOC). Freemasonry was introduced by European communities with the establishment of the first lodge, La Choisie, in Batavia (now Jakarta) in 1764, founded by Radermacher, a key figure who also co-founded the Bataviaasch Genootschap van Kunsten en Wetenschappen (Batavian Society of Arts and Sciences), an institution that later became highly influential in the Dutch East Indies. This research employs the historical method, encompassing the stages of heuristic research, source criticism, interpretation, and historiography. Primary sources include the Woordenboek voor Vrijmetselaren, Geschiedenis der Vrijmetselarij, various Masonic history books, and archival materials from lodges in Java. The research findings indicate that the establishment of Freemasonry lodges across various cities in Java and Sumatra served as the main avenue for disseminating Enlightenment ideals and fostering social networks among the colonial elite. Early challenges faced by Freemasonry included resistance from both colonial authorities and the church. The founding of lodges such as  La Choisie (1764), La Fidèle Sincérité (1769), and La Vertueuse (1769) illustrates the social dynamics prevalent in Batavia, where European officials, traders, and entrepreneurs formed connections through Masonic networks. This research contributes to the field of social history, where spiritual associations are often underrepresented in conventional historical analyses. Additionally, this study provides a deeper understanding of colonial history and highlights the role of transnational networks in shaping the societal dynamics of colonial Southeast Asia